Immune Cells in Cancer Therapy and Drug Delivery. (24th April 2016) - Eyileten, Ceren; Majchrzak, Kinga; Pilch, Zofia; Tonecka, Katarzyna; Mucha, Joanna; Taciak, Bartlomiej; Ulewicz, Katarzyna; Witt, Katarzyna; Boffi, Alberto; Krol, Magdalena; Rygiel, Tomasz P.
Abstract : Recent studies indicate the critical role of tumour associated macrophages, tumour associated neutrophils, dendritic cells, T lymphocytes, and natural killer cells in tumourigenesis. These cells can have a significant impact on the tumour microenvironment via their production of cytokines and chemokines. Additionally, products secreted from all these cells have defined specific roles in regulating tumour cell proliferation, angiogenesis, and metastasis. They act in a protumour capacity in vivo as evidenced by the recent studies indicating that macrophages, T cells, and neutrophils may be manipulated to exhibit cytotoxic activity against tumours. Therefore therapy targeting these cells may be promising, or they may constitute drug or anticancer particles delivery systems to the tumours. Herein, we discussed all these possibilities that may be used in cancer treatment.